Kevin C. Karnes, Music, Criticism, and the Challenge of History: Shaping Modern Musical Thought in Late Nineteenth-Century Vienna (2008) (Journal of the Society for Musicology in Ireland, 2009)
A review of Kevin C. Karnes, Music, Criticism, and the Challenge of History: Shaping Modern Musical Thought in Late Nineteenth-Century Vienna (Oxford: Oxford University Press, 2008), ISBN 978-0-19-536866-6